A Critical Review and Scientific Prospective on Contraceptive Therapeutics from Ayurveda and Allied Ancient Knowledge - Bhatt, Narendra; Deshpande, Manasi (Frontiers in Pharmacology, 2021)
Commonly used synthetic or prescribed hormonal drugs are known to interfere with the endocrine system and may have adverse reproductive, neurological, developmental, and metabolic effects in the body. These may also produce adverse effects such as polycystic ovarian disorder, endometriosis, early puberty, infertility or toxicity to gonads, testicular germ cell cancer, breast or prostate cancer, brain developmental problems, and even birth defects. Globally, there is a strong emergence of interest in natural products for reproductive health that offers opportunities for new contraceptive developments. The search for alternate safer contraceptive product or agent of natural origin is of scientific interest. Ayurvedic / classical texts offer knowledge and information about reproductive function and therapeutics including those for enhancement and limiting male and female fertility. Review of ancient, medieval and recent - including texts on erotica provide information on approaches and large numbers of formulations and drugs of plant, mineral or animal origin that are claimed to have sterilizing, contraceptive, abortifacient and related properties is presented. Few among these are known to be toxic and few are not so common. However, most of the formulations, ingredients or modes of administration have remained unattended due to issues related to consumer compliance and limitations of standardization and lack of appropriate validation modalities. Several of these ingredients have been studied for their phytoconstituents and variety of pharmacological activities. There have been efforts to standardize several classical dosage forms and attempts to adapt to modern technologies. List of formulations, ingredients, their properties, linked with known constituents, pharmacological, biological and toxicity studies are given in a series of tables. Possible effectiveness and safety of selected formulations and ingredients are examined. Suggestions based on new drug delivery systems integrated with advances in biotechnology, to provide prospects for new therapeutics for contraception are considered. Ayurveda is built on wholistic paradigm of biological entity rather than limited gonadal functions. Graphic presentation of few of carefully chosen hypotheses are proposed. New approaches to standardization and ethnopharmacological validation of natural contraceptive therapeutics may offer novel mechanisms and modalities and therapeutic opportunities to satisfy unmet needs of contraception.